The Influence of Training, Work Environment and Discipline on Performance and Job Satisfaction - Depari, Marisa Yunita Br (PT FORMOSA CENDEKIA GLOBAL, 2023)
Previous research or relevant research is very important in research or scientific articles. Previous research or relevant research functions to strengthen theories and phenomena of the relationship or influence between variables. This article reviews the Influence of Job Satisfaction and Performance: Analysis of Training, Work Environment and Discipline, a Study of Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Training influences job satisfaction; 2) The work environment influences job satisfaction; 3) Discipline influences job satisfaction; 4) Training influences performance; 5) The work environment influences performance. 6) Discipline influences performance and 7) Job satisfaction influences performance